Neurophychiatric symptoms in anti-N-methyl-D-aspartate receptor encephalitis: apropos of two cases - Custodio, N. (2016)
Encephalitis against N-methyl-D-aspartate receptor (NMDAR) is included in the group of autoimmune encephalitis. It is more common in women in reproductive age. The first clinical features may be similar to viral infections prodromes. It is sometimes related to neoplasms. The accurate diagnosis and early administration of immunomodulatory therapy is critical to the prognosis. In this article, a review of the literature was performed and two cases of anti-NMDAR encephalitis in different stages of life are presented.